2019
DOI: 10.1093/brain/awz258
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and mapping language, attention and executive multidimensional deficits in stroke aphasia

Abstract: Despite being potentially crucial for performance, recovery and rehabilitation, non-verbal cognitive functions have not been investigated comprehensively in patients with post-stroke aphasia. By administering a battery of tests of attention and executive function, Schumacher et al. identify six orthogonal non-verbal and language components that are associated with separable structural correlates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 82 publications
(145 reference statements)
13
119
0
Order By: Relevance
“…We could speculate that this result might reflect variation in another form of executive process (distinct from the executive process that seems to be captured by the second factor), which might be involved in (i) iteratively generating and assessing semantic associations (Camel and Cactus and synonym judgement); (ii) generating speech (words per minute and total words produced); and (iii) generating and monitoring ‘chunks’ to complete the backwards digit span task. Indeed, Schumacher et al (2019) found that the Camel and Cactus test loaded onto an ‘Inhibit-Generate’ executive component. However, without more measures of attention and executive function it is not possible to test these speculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could speculate that this result might reflect variation in another form of executive process (distinct from the executive process that seems to be captured by the second factor), which might be involved in (i) iteratively generating and assessing semantic associations (Camel and Cactus and synonym judgement); (ii) generating speech (words per minute and total words produced); and (iii) generating and monitoring ‘chunks’ to complete the backwards digit span task. Indeed, Schumacher et al (2019) found that the Camel and Cactus test loaded onto an ‘Inhibit-Generate’ executive component. However, without more measures of attention and executive function it is not possible to test these speculations.…”
Section: Resultsmentioning
confidence: 99%
“…These new approaches are based on the second source of individual differences noted above—namely, graded variations along continuous behavioural dimensions. Recent studies have reconceptualized the variations in PSA as forming an aphasic multidimensional space with each patient taking up a different position (typically varying in terms of phonology, semantics, speech fluency and, when assessed, non-language cognitive skills) ( Butler et al , 2014 ; Halai et al , 2017, 2018 a ; Schumacher et al , 2019 ). In this formulation, the classical aphasia labels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Non-classical two-dimensional scaling was performed on this dissimilarity matrix (Shepard, 1980). Second, we looked for patterns of covariation in the presence or absence of clinical features (Perry et al, 2017;Grisanzio et al, 2018;Schumacher et al, 2019). We grouped the forty-five binary clinical features into twenty-four groups of related features by summing the number of present features in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke aphasia (PSA) is prevalent (Engelter et al, 2006) and debilitating (Tsouli et al, 2009), and there is increasing awareness that deficits in non-verbal cognitive processing might contribute to language performance in such individuals (Robson et al, 2013;Geranmayeh et al, 2014;Schumacher et al, 2019). Indeed, there is evidence from multiple aetiologies including congenital amusia (Foxton et al, 2004;Foxton et al, 2006), developmental dyslexia (Witton et al, 1998), specific language impairment (Corriveau et al, 2007), children who stutter (Wieland et al, 2015) and primary progressive aphasia (Goll et al, 2010;Grube et al, 2016) that language impairment can co-occur with more fundamental deficits in auditory processing, just as auditory processing abilities associate with language performance in healthy children (Grube et al, 2012) and adults .…”
Section: Introductionmentioning
confidence: 99%